Trade policy in the 1980s - Cline, William R.; Institute for International Economics (U.S.) (Washington, DC : Institute for International Economics ; Cambridge [Mass.] : Distributed by MIT Press, 1983)
In 1982 the Institute for International Economics held a conference to examine past and prospective trade issues and to consider the proper design for trade policy in the 1980s.This volume reports the conference proceedings in full, with additional comments on the outcome of the General Agreement on Tariff and Trade (GATT) Ministerial.
Papers prepared for "Trade policy in the 1980s," a conference held at the Institute for International Economics in Washington, June 23-25, 1982.
Includes bibliographical references and indexes.
rpm 23/01/2019
Loans
Keywords: Commercial policy; Commerce